1987
DOI: 10.1136/sti.63.3.160
|View full text |Cite
|
Sign up to set email alerts
|

Serological ecology of Neisseria gonorrhoeae (PPNG and non-PPNG) strains: Canadian perspective.

Abstract: One hundred and thirty eight penicillinase producing Neisseria gonorrhoeae (PPNG) and 239 non-PPNG strains were characterised serologically using a panel of seven monoclonal antibodies directed against protein IA and seven against protein lB. An association between serovar and susceptibility to antimicrobial agents, auxotype, and plasmid content was observed. Serogroup WI strains were more sensitive to penicillin, ampicillin, tetracycline, erythromycin, cefoxitin, and cefuroxime. Sixty five (82%) of the 79 WI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 27 publications
4
14
0
Order By: Relevance
“…In several studies, other 1-lactams such as cefmetazole (26), cefotetan (59), and cefuroxime (40) showed diminished in vitro potency for CMRNG compared with penicillin-susceptible strains. In some cases, there was a weaker association between the MIC of penicillin and those of spectinomycin and tetracycline (61).…”
Section: Benefits and Problems Of Astmentioning
confidence: 99%
See 1 more Smart Citation
“…In several studies, other 1-lactams such as cefmetazole (26), cefotetan (59), and cefuroxime (40) showed diminished in vitro potency for CMRNG compared with penicillin-susceptible strains. In some cases, there was a weaker association between the MIC of penicillin and those of spectinomycin and tetracycline (61).…”
Section: Benefits and Problems Of Astmentioning
confidence: 99%
“…Since 1976, the PPNG phenotype has been found in most countries, and it has been associated with many different serotypes and auxotypes. For example, in a 1987 Canadian survey (26), 138 PPNG phenotypes were distributed among 14 different serovars, several auxotypes, and several plasmid profiles. This reflects both strain geographic dispersion and sharing of plasmids among strains.…”
Section: Benefits and Problems Of Astmentioning
confidence: 99%
“…CHROMOSOMAL RESISTANCE In retrospective studies of N. gonorrhoeae strains isolated in the prepenicillin era (i.e., before 1944), many isolates were V-LACTAMASE PLASMIDS AND ANTIBIOTIC RESISTANCE S129 (13,18,19,34). Chromosomal resistance to one antibiotic often reduced the efficacy of other unrelated antimicrobial agents by virtue of cross-resistance to them (34,46,68).…”
Section: Molecular Biology Andevolution Of P-lactamase Plasmids Inmentioning
confidence: 99%
“…A number of typing methods have been developed for N. gonorrhoeae based on growth requirements for specific nutrients and cofactors (1), antibiotic sensitivity (3,20), differences in electrophoretic mobility of bacterial enzymes (17), and serological reactivity against surface antigens (12). The introduction of PCR and high-throughput nucleotide sequencing has led to the development of several DNA-based typing methods.…”
mentioning
confidence: 99%